Is Empowerment Influencing Domestic Violence against Women in Karnataka?. - Mutharayappa, R. and Dhak, Biplab (2010)
The main focus of the study is to examine the factors affecting domestic violence and to understand whether women‘s empowerment has any influence on domestic violence. Keeping this in view, the data available from the National Family Health Surveys (NFHS) 1998–99 and 2005–06 were used. Data reveals that about three out of every five women agrees with at least one reason of wife-beating is justified. The main reason for the women who agree wife beating is justified when the wife neglects house or children followed by the wife who goes out without telling her husband and the husband suspect wife is unfaithful. About 42 per cent of women experienced different forms of violence. Women who experience sexual violence also experience more severe forms of emotional and physical violence. Women who have higher education in the household enjoy higher household autonomy and such women experience less domestic violence. Couples who are of equal age and education experience lowest prevalence of physical, sexual or emotional violence. When the husband does not earn any money for the family, a higher percentage of women experienced physical, sexual and emotional violence. Data shows that about two-third of women reported physical violence since their husbands do not earn any money. Women who earn more than their husbands about 29 per cent, experienced physical violence. When women’s earnings are equal to their spouses, sexual violence is less.